PENGARUH PENAMBAHAN PUPUK TERHADAP PRODUKSI JAMUR TIRAM - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1989)
The media used in the experiment were sawdust of eight wood species mixed with 1% calcium carbonate (CaC03), 1% gypsum, 0.5% fertilizers i.e. urea, ammonium sulphate (ZA), KCL, NPK and trisuperphosphate (TSP) and distilled water, respectively. The substrate was cooled after autoclave sterilization before being inoculated with pure culture of oyster mushroom. The mature mushrooms were harvested daily after the growth of fruiting body.The media started producing mushroom two months after inoculation (28 - 45 days). The highest yield was obtained from rubberwood sawdust mixed with ZA (362.43 g) and the lowest yield was on teak sawdust containing urea (90.14 g) per 500 grams media. Media from rubberwood, weru, jeungjing and pulai sawdust were suitable for mushroom culture. Fertilizer supplement seems to improve mushroom yield. ZA, urea were more effective than KCL fertilizer for mushroom production.The average Biological Efficiency (BE) of entire treatments was 84.32% (35.25-140.23%). The relatively high BE was obtained from weru, rubber and jeungjing and the lowest BE was on teak sawdust media.